2009
DOI: 10.1002/jmri.21899
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive adenosine stress perfusion MRI defines the etiology of chest pain in the emergency room: Comparison with nuclear stress test

Abstract: Purpose-To compare standard of care nuclear SPECT imaging with cardiac magnetic resonance imaging (MRI) for emergency room (ER) patients with chest pain and intermediate probability for coronary artery disease.Materials and Methods-Thirty-one patients with chest pain, negative electrocardiogram (ECG), and negative cardiac enzymes who underwent cardiac single photon emission tomography (SPECT) within 24 h of ER admission were enrolled. Patients underwent a comprehensive cardiac MRI exam including gated cine ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The present study extends the findings of previous investigations (21)(22)(23)(24)(25). Both Kwong et al (23) and Cury et al (21) showed the value of cardiac MR imaging in patients seen in the ED.…”
Section: Cardiac Imaging: Stress Cardiac Mr Imaging Compared With Strsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study extends the findings of previous investigations (21)(22)(23)(24)(25). Both Kwong et al (23) and Cury et al (21) showed the value of cardiac MR imaging in patients seen in the ED.…”
Section: Cardiac Imaging: Stress Cardiac Mr Imaging Compared With Strsupporting
confidence: 91%
“…Moreover, there was no comparison with a separate stress imaging modality. Similar to the Ingkanisorn et al study, the investigations by Lerakis et al (24) and Vogel-Claussen et al (25) yielded encouraging findings regarding the utility of stress cardiac MR imaging; however, the former is a retrospective analysis and the latter included only 27 patients.…”
Section: Cardiac Imaging: Stress Cardiac Mr Imaging Compared With Strmentioning
confidence: 60%
See 1 more Smart Citation
“…MRI can also differentiate between chronic and acute infarcts 6 , so its use in triaging chest-pain in the emergency-room may grow 10, 11 .…”
mentioning
confidence: 99%
“…Evaluating patients presenting to the ED with suspected ACS, Vogel-Claussen et al 65 studied the prognostic importance of the size and duration of perfusion defects identified during perfusion stress. In ED patients with chest pain at an intermediate probability for coronary artery disease, Vogel-Claussen et al 65 demonstrated that diffuse subendocardial hypoperfusion defects (less than half of the myocardial wall thickness in at least 2 different coronary artery territories of 6 beats in duration) were associated with return to the ED with chest pain compared with patients who had no CMR perfusion defect ( P = 0.02).…”
Section: Emergency Department Assessmentsmentioning
confidence: 99%